The student voice in quality assurance: what factors make for a great GP placement in the eyes of undergraduate medical students? - Simon Thornton; Trevor Thompson; Maria Gresham; Alice James (BMC Medical Education)
Abstract Background With general practice becoming an increasingly important part of undergraduate medical education, it is vital to have reliable ways for assessing placement quality. The most prevalent tools for such assessment are the Dundee Ready Education Environment Measure (DREEM) and the Manchester Clinical Placement Index (MCPI). These instruments were not specifically designed for use only in GP contexts and were developed without student involvement at inception. As a result, they may omit quality indicators valued by students on GP placement. This study sought to understand the quality of learning in GP from the student perspective and compare this to what is assessed by DREEM and MCPI. We hope the results of this study will inform the development of placement quality questionnaires inspired by the student voice. Methods Purposive sampling was used to recruit 17 undergraduate medical students in academic years 3–5 at the University of Bristol into four focus groups. These ran from May 2023 to April 2024 and were based on a topic guide developed and agreed on by all authors. Theoretical saturation was achieved as no new themes emerged in the final focus group. The focus groups were recorded and transcribed in full. The transcripts underwent systematic coding using NVivo. The codes formed the basis for the thematic analysis. Results Four main themes emerged: a sense of belonging, quality of learning, efficiency of learning, and the qualities of the GP teacher. These themes are illustrated by pertinent quotes from the focus groups. Subthemes included being given appropriate clinical autonomy within the placement, timely access to resources, structured clinical activities, and tutor qualities such as enthusiasm and leadership. Conclusions This paper offers a new perspective on the quality of GP placements by focusing on the student experience. It identifies themes and subthemes that education teams should assess, beyond what's covered by existing tools like MCPI and DREEM. These include students’ sense of belonging, perceived learning efficiency, and appropriate clinical autonomy. We argue that ignoring these areas neglects key aspects of student needs. We are piloting a new questionnaire incorporating these themes to better identify substandard placements and improve student experiences.